An Analysis of the Sorts of Practical Contradiction in the Jurisprudence and Morality focusing on the Practical Contradiction Of Consideration in the Morality - Mohsen Shokouhbakhsh; fathollah najarzadegan; MOHAMMAD ALEMZADEH NOORI; Mohammad Kazem Rahman Setayesh (اخلاق وحیانی, 2019)
One of the important subjects in the science of the principle of jurisprudence, having abundant applications in the jurisprudence and morality, is the practical contradiction. Considering the differences of jurisprudence and morality, the contradiction normally raised in morality has considerable differences with one of jurisprudence about the definition, division and preferrers (Morajjehat). In this paper, first, we design a new frame for the contradiction in the principle of moral jurisprudence. Second, for some moral affairs having considerable role in the explanation of Islamic lifestyle, a new sort of contradiction will be raised called practical contradiction of consideration. In this contradiction, in contrast to the judgmental contradiction, the committed man has the ability to do both contradictory actions, but it is not obligatory or he cannot use the time and power for both actions. Consequently, he must focus on the most important one. Reviewing the scriptures valuating actions, it seems that the key to understating some narrations is the practical contradiction of consideration. Since this sort of practical contradiction is defined in the domain of morality and its preferrers are different from the judgmental contradiction, the result of it in some cases is different from the judgmental contradiction in the jurisprudence.